2019
DOI: 10.1002/brb3.1426
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio predicts post‐thrombolysis early neurological deterioration in acute ischemic stroke patients

Abstract: Background and purpose Intravenous thrombolysis (IVT) has become the standard treatment for acute ischemic stroke within 4.5 hr after symptoms onset. However, a fraction of patients would develop early neurological deterioration (END) after IVT. The aim of our study was to explore the utility of neutrophil–lymphocyte ratio (NLR) in predicting END. Methods From October 2016 to March 2018, 342 consecutive patients with thrombolytic therapy were prospectively enrolled in this study. Blood cell counts were sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 30 publications
(49 reference statements)
1
38
0
Order By: Relevance
“…Several inflammatory biomarkers was reported to be correlated with neurological deterioration in patients with acute ischemic stroke, such as lipoprotein-associated phospholipase A2, [16]. neutrophil–lymphocyte ratio [17] and so on. Previous studies have revealed that high-sensitivity C-reactive protein (hs-CRP) may act as an inflammatory factor that responds to ischemic stroke [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory biomarkers was reported to be correlated with neurological deterioration in patients with acute ischemic stroke, such as lipoprotein-associated phospholipase A2, [16]. neutrophil–lymphocyte ratio [17] and so on. Previous studies have revealed that high-sensitivity C-reactive protein (hs-CRP) may act as an inflammatory factor that responds to ischemic stroke [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte counts have been considered to have neuroprotective effect and contribute to neurological function improvement [36]. Both peripheral monocytes and neutrophils could perform as the source of matrix metalloproteinase-9, which would lead to HT and symptomatic deterioration [7,37,38]. Furthermore, it is reported that neutrophils can induce free oxygen radicals and cause brain injury [39].…”
Section: Discussionmentioning
confidence: 99%
“…In case of disagreement about the NIHSS score evaluation, a third neurologist in this center was invited for a nal decision. Post-thrombolysis END was de ned as an increase in the NIHSS score by ≥ 4 points in the total score within 24 hours after thrombolysis [7,24,25].Meanwhile, post-thrombolysis ENI was de ned as a decrease in the NIHSS score by ≥ 4 points in the total score or a complete resolution of neurological de cits within 24 hours after thrombolysis [26][27][28].…”
Section: De Nition Of Post-thrombolysis Early Neurological Deterioratmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the association between HAR and sICH after endovascular treatment are not total clear, and further studies are warranted. In term of previous researches, in ammation plays an important role in the pathophysiological mechanism of ischemic stroke [30][31][32][33] . Oxidative stress and in ammatory activity could lead to blood brain barrier disruption, which may be linked to hemorrhagic transformation after endovascular treatment [34] .…”
Section: Discussionmentioning
confidence: 99%